TRIBUTES TO SPAIN: HISTORICAL CONTEXT AND INFLUENCES ON THE PRODUCTION OF ESPAÑA ELEMENTAL BY ALEJANDRO ROMUALDO - Mitma Navarro, Adrián Alejandro (2021)
The purpose of this work is to search the rhetorical field that allowed the emergence of España Elemental; that is why, and following Arduini's approaches, we will observe the historical and political context within which it occurs. We will also see if the division that took place of the Generation of fifty (pure and social poetry) is still relevant, and we will try to identify what tendency Alejandro Romualdo might belong to. We will also carry out a review of what the review of the work of the Peruvian poet has commented on. Finally, we will dely into the poem España Elemental in order to highlight the influences and function that the text was trying to fulfill, which we propose is the revitalization of Spain and pay homage to it.